Programing the rewinding of a three-phase induction motor stator using interactive computer-aided design technique - Ike, Samuel; Peter, Enyong; Olowu, T. (International Journal of Engineering and Technology, 2015)
In this paper, a computer program was developed in MATLAB programming language and applied in the refurbishment of defective three-phase squirrel-cage induction motor using the computer-aided design technique/approach. The MATLAB programming language and Computer-Aided Design (CAD) analysis adopted aided the fast computation and convergence of a output result from the developed program that was used in the practical refurbishment of a defective 48-slot 3-phase squirrel-cage induction motor as well as the production of the entire stator winding. The result also revealed the motor as being a 4-pole type which lends itself easily to the lap winding pattern. The winding was practically developed using the program result data, installed, connected and tested. The speed realized from the post-refurbishment workshop test-running using the stroboscopic speed measuring instrument was 1500rpm. This was considered as good performance on no-load condition. The machine was allowed to run for about one hour during the workshop test-running without overheating. The computed output power was 20 kW. The estimated efficiency and power factor by CAD technique were 90 % and 0.9, respectively. These values were considered satisfactory.
Keywords: Induction Motor; Refurbishment; Cad; Matlab.